A comparative study on the mode of interaction of different nanoparticles during MALDI‐MS of bacterial cells. (9th January 2013) - Gopal, Judy; Manikandan, M.; Hasan, Nazim; Lee, Chia‐Hsun; Wu, Hui‐Fen
<x xml:space="preserve">Abstract</x> We propose the benefits of preincubation during nanoparticle‐assisted bacterial analysis, where the bacteria are grown along with the nanoparticles. We were able to obtain a two to ten fold enhancement of bacterial signals in 3 h compared to the generally used methodology followed in previous literature. The previous literature method required a long time (18 h) to obtain such an enhancement. We probe the interactions of two bacteria, Staphylococcus aureus and Pseudomonas aeruginosa, with Ag, NiO, Pt TiO2 and ZnO nanoparticles via transmission electron microscopy, ultraviolet spectroscopy and matrix‐assisted laser desorption/ionization (MALDI) mass spectrometry (MS). Based on these results, we propose a mechanism for interaction of these five nanoparticles with bacteria. Two mechanisms were observed for the interactions: (1) Mechanism A is proposed for the Pt and NiO NPs which functioned based on affinity for bacterial cells. (2) Mechanism B was proposed for the bactericidal NPs such as TiO2, ZnO and Ag NPs. The results indicate that the success of the unmodified NPs in MALDI‐MS bacterial studies lies in following the ideal protocol for incubation at the ideal concentrations. Copyright © 2013 John Wiley & Sons, Ltd.